2006
DOI: 10.1007/s00192-006-0131-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in women with multiple sclerosis and overactive bladder syndrome

Abstract: The aim of this study was to evaluate the impact of symptoms of overactive bladder syndrome (OAB) on the quality of life (QoL) in female patients with or without multiple sclerosis (MS) and their correlation with findings from urodynamics (UDS). We enrolled 107 female patients with clinically definite MS and urinary symptoms of OAB. One-hundred female patients with similar OAB symptoms were used as a control group. Data on OAB symptoms, onset and progression, and results of any previous investigation were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 23 publications
2
43
0
1
Order By: Relevance
“…Urinary urgency, intermittent urine stream, and UUI were found to be the most significant predictors of seeking treatment, with patients who had these symptoms being 20%, 40%, and 78% more likely to seek treatment, respectively, than those without these symptoms. Symptoms of urgency and UUI in particular have previously been shown to significantly impair HRQOL 6,24,25 ; thus it is not entirely surprising that they are among the key factors driving patients to seek treatment. This observation is in contrast to the EpiLUTS study, which showed that urinary frequency was the significant symptom predictor of seeking treatment in both men and women with OAB symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary urgency, intermittent urine stream, and UUI were found to be the most significant predictors of seeking treatment, with patients who had these symptoms being 20%, 40%, and 78% more likely to seek treatment, respectively, than those without these symptoms. Symptoms of urgency and UUI in particular have previously been shown to significantly impair HRQOL 6,24,25 ; thus it is not entirely surprising that they are among the key factors driving patients to seek treatment. This observation is in contrast to the EpiLUTS study, which showed that urinary frequency was the significant symptom predictor of seeking treatment in both men and women with OAB symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Urologic manifestations are one of the most well-known components of the disease, with more than 90% of patients with MS experiencing urologic symptoms 10 years after disease onset. 3 Symptoms relating to the bladder and bowel are often considered to be among the most distressing facets of the disease, 4 and urinary symptoms have been shown to have a detrimental effect on health-related quality of life (HRQOL) in patients with MS. [5][6][7][8] Although the presence of bladder dysfunction in patients with MS is well established, information on the types and prevalence of specific lower urinary tract symptoms (LUTS) is sparse, as they are not routinely or comprehensively assessed. Furthermore, it is unclear how often urinary symptoms are assessed and treated during routine evaluations of patients with MS. As health-care providers (HCPs) may be focused on treating the neurodegenerative symptoms of MS, LUTS may be overlooked, and as such, may not be adequately and properly managed.…”
mentioning
confidence: 99%
“…MS patients have larger PVR volumes than their control counterparts, 29,30 and mean PVR is greater in MS patients with recurrent UTIs than in those without. 31 Other important evaluation tools are three-day voiding or catheterization diaries, urine analysis, and culture.…”
Section: Basic Testingmentioning
confidence: 99%
“…The domains of physical health, physical role limitations, health, perception and sexual function do show a trend towards increased QoL. Since lower urinary tract symptoms cause a substantial decrease in quality of life also in MS patients we expected that the improvement in lower urinary tract symptoms would have caused improvements in other domains of the MS-QoL 54 as well [16]. Therefore we think that the study is too small to show this effect.…”
Section: Discussionmentioning
confidence: 91%